Comprehensive analysis of the effects of P4ha1 and P4ha2 deletion on post-translational modifications of fibrillar collagens in mouse skin - Sarohi, Vivek (Frontiers in Cell and Developmental Biology, 2025)
IntroductionCollagens, the most abundant proteins in mammals, play pivotal roles in maintaining tissue structure, functions, cell-to-cell communication, cellular migration, cellular behavior, and growth. Structures of collagens are highly complex due to the presence of dynamic post-translational modifications (PTMs), such as hydroxylations (on prolines and lysine residues) and O-glycosylation (on hydroxylysines) enzymatically catalyzed during biosynthesis in the endoplasmic reticulum. Collagen PTMs are essential for maintaining structural stability, elasticity, and different functions of collagens. The most prevalent modification in fibrillar collagens is prolyl 4-hydroxylation catalyzed by collagen prolyl 4-hydroxylases (C-P4Hs). Prolyl 4-hydroxylation on collagens plays a critical role in collagen biosynthesis, thermostability, and cell-collagen interactions. Collagens are large proteins. Different regions of collagen perform different functions, so the presence or absence of a PTM on a particular collagen site can affect its functioning. However, comprehensive site-specific identification of these PTMs on fibrillar collagen chains of mice skin has not been performed yet. Furthermore, the effects of prolyl 4-hydroxylase alpha 1 (P4HA1) and P4HA2 on 3-hydroxyproline, 5-hydroxylysine, and O-glycosylation sites of fibrillar collagen chains have not yet been explored.MethodologyThis study presents a comprehensive PTM analysis of fibrillar collagen chains extracted from the skin of different mutants of C-P4Hs (P4ha1+/−; P4ha2−/−, P4ha1+/+; P4ha2−/−, P4ha1+/−; P4ha2+/−, P4ha1+/+; P4ha2+/−) and wild-type mice. In this study, proteomics-based comprehensive PTM site identification by MS2 level ions from raw mass spectrometry data was performed, and MS1-level quantification was performed for PTM occupancy percentage analysis.Results and discussionA total of 421 site-specific PTMs were identified on fibrillar collagen chains (COL1A1, COL1A2, and COL3A1) extracted from wild-type mice skin. A total of 23 P4HA1-specific and seven P4HA2-specific 4-hydroxyproline sites on fibrillar collagen chains were identified. Moreover, it was found that the P4ha1 and P4ha2 deletion can affect the 3-hydroxyproline occupancy percentages in mice skin. Interestingly, increased levels of lysyl 5-hydroxylation were detected upon partial deletion of P4ha1 and full deletion of P4ha2. These findings show that the effects of deletion of prolyl 4-hydroxylases are not limited to less 4-hydroxylation on some specific proline sites, but it can also modulate the prolyl 3-hydroxylation, lysyl 5-hydroxylation, and O-glycosylation occupancy percentages in the fibrillar collagen chains in a site-specific manner.